Heat shrinkable behavior, physico-mechanical and structure properties of electron beam cross-linked blends of high-density polyethylene with acrylonitrile-butadiene rubber. (March 2016) - Reinholds, Ingars; Kalkis, Valdis; Merijs-Meri, Remo; Zicans, Janis; Grigalovica, Agnese
Abstract: In this study, heat-shrinkable composites of electron beam irradiated high-density polyethylene (HDPE) composites with acrylonitrile-butadiene rubber (NBR) were investigated. HDPE/NBR blends at a ratio of components 100/0, 90/10, 80/20, 50/50 and 20/80 wt% were prepared using a two-roll mill. The compression molded films were irradiated high-energy (5 MeV) accelerated electrons up to irradiation absorbed doses of 100–300 kGy. The effect of electron beam induced cross-linking was evaluated by the changes of mechanical properties, gel content and by the differences of thermal properties, detected by differential scanning calorimetry. The thermo-shrinkage forces were determined as the kinetics of thermorelaxation and the residual shrinkage stresses of previously oriented (stretched up to 100% at above melting temperature of HDPE and followed by cooling to room temperature) specimens of irradiated HDPE/NBR blends under isometric heating–cooling mode. The compatibility between the both components was enhanced due to the formation of cross-linked sites at amorphous interphase. The results showed increase of mechanical stiffness of composites with increase of irradiation dose. The values of gel fraction compared to thermorelaxation stresses increased with the growth of irradiation dose level, as a result of formation cross-linked sites in amorphous PP/NBR interphase. Highlights: Binary blends of HDPE/NBR have been irradiated with 5 MeV accelerated electrons. Increase of NBR content and irradiation dose improves cross-linking efficiency. Thermo-shrinkage and residual stresses are investigated for oriented specimens. Cross-linked HDPE/NBR composites can be successfully used as thermos-shrinkable materials.